If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 102 = -2 + 8(1 + 6x) 102 = -2 + (1 * 8 + 6x * 8) 102 = -2 + (8 + 48x) Combine like terms: -2 + 8 = 6 102 = 6 + 48x Solving 102 = 6 + 48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48x' to each side of the equation. 102 + -48x = 6 + 48x + -48x Combine like terms: 48x + -48x = 0 102 + -48x = 6 + 0 102 + -48x = 6 Add '-102' to each side of the equation. 102 + -102 + -48x = 6 + -102 Combine like terms: 102 + -102 = 0 0 + -48x = 6 + -102 -48x = 6 + -102 Combine like terms: 6 + -102 = -96 -48x = -96 Divide each side by '-48'. x = 2 Simplifying x = 2
| 226=5-y | | 6y-4+5(2y+1)=-2(y+7) | | 180=-6(-5r+5) | | -v+278=46 | | 23x-129=14x-66 | | 7n+8=3n-12 | | y-28=2 | | 8(2+7p)=128 | | 12x-51=68-27 | | X^2-80x-4000=0 | | -4(-4w+2)-2w=4(w-5)-6 | | 6x-15+6=15-25x+6x | | 6x-47=4x-31 | | 40+2+5x=95 | | -45=3x(2-7) | | (x+5)3-30=0 | | 14+6a-8=-10 | | 5x^2+2-11=0 | | 6x-21=15-31x | | 7x=2x+65 | | Y=7x^2-28x+14 | | 0.05(-20-8)=0.07(20) | | 7x+5=11x-27 | | (n+1)*4=36 | | 5.4=logx | | Y=5x+20x+10 | | -8.4x=50.4 | | 30x+6y=27 | | t-10=8 | | f(x)=4x^2-25+0 | | (8x+24)+(9y+81)=8(x+3)+9(y+9) | | 125=5(5x+5) |